Tobacco Use of the World and in Turkey and Tobacco Control Policy an Overview - Pesen, Süleyman Furkan; Karadoğan, Seyfullah; Akbulut, Aykut (Turkey Health Literacy Journal, 2021)
Using tobacco is one of the most important public health problem for all countries.In this review, Turkey and world tobacco using statistic, moral consequences, politics of diminishing usage of tobacco, accomplished works with these politics and results is that we wish to give information.The life loss of the most addicted and most worldwided material,which is tobacco, is given most important thing of fighting against it.With this regard, MPOWER pack which is politics of controlling tobacco will be given information about it.In the world andTurkey, we will give knowledge about what is done which regards of tobacco.Health consequences of tobacco, diseases which is causedby tobacco, and physical and moral consequences of these diseases will be recovered.Economic trouble of mortality and morbidity of tobacco using is given information also.Tobacco using is also effects passive smokers, we will give knowledge about that.In additionFramework Convention on Tobacco Control (FCTC) and National Tobacco Control Program (NTCP) will be introduced to you.
Keywords: Tobacco, Health, Tobacco Control, Epidemiyology.